Cerebral vasomotor reactivity during hypo- and hypercapnia in sedentary elderly and Masters athletes - Zhu, Yong-Sheng (Nature Publishing Group, 2013)
Physical activity may influence cerebrovascular function. The objective of this study was to determine the impact of life-long aerobic exercise training on cerebral vasomotor reactivity (CVMR) to changes in end-tidal CO2 (EtCO2) in older adults. Eleven sedentary young (SY, 27±5 years), 10 sedentary elderly (SE, 72±4 years), and 11 Masters athletes (MA, 72±6 years) underwent the measurements of cerebral blood flow velocity (CBFV), arterial blood pressure, and EtCO2 during hypocapnic hyperventilation and hypercapnic rebreathing. Baseline CBFV was lower in SE and MA than in SY while no difference was observed between SE and MA. During hypocapnia, CVMR was lower in SE and MA compared with SY (1.87±0.42 and 1.47±0.21 vs. 2.18±0.28 CBFV%/mm Hg, P<0.05) while being lowest in MA among all groups (P<0.05). In response to hypercapnia, SE and MA exhibited greater CVMR than SY (6.00±0.94 and 6.67±1.09 vs. 3.70±1.08 CBFV1%/mm Hg, P<0.05) while no difference was observed between SE and MA. A negative linear correlation between hypo- and hypercapnic CVMR (R(2)=0.37, P<0.001) was observed across all groups. Advanced age was associated with lower resting CBFV and lower hypocapnic but greater hypercapnic CVMR. However, life-long aerobic exercise training appears to have minimal effects on these age-related differences in cerebral hemodynamics.